Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar IPS Siswa Kelas V di UPTD SD Negeri 125543 Pematangsiantar - Diana Galingging; Aprido.B. Simamora; Eva Pasaribu (CV Putra Publisher, 2024)
This research aims to see the influence of the Mind Mapping Learning Model on the Social Sciences Learning Outcomes of Class V Students at Uptd Sd Negeri 125543 Pematangsiantar. The population in this study were all students in class V UPTD SD Negeri 125543 Pematangsiantar with a total of 22 students. So the sample that will be used in this research is Nonprobability Sampling, and the entire population will be studied. Many students in research at UPTD SD Negeri 125543 Jl. Farel Pasaribu No. 76 totaling 22 people consisting of 8 men and 14 women. Based on the results of the data that researchers obtained with this research, it is to answer the problem formulation, namely